Combined perioperative plasma endoglin and VEGF-A assessment in colorectal cancer patients. - Bogusław Kedra; Adam Kukliński; Krystyna Pawlak; Piotr Myśliwiec (Folia Histochemica et Cytobiologica, 2009)
Colorectal cancer growth and spread is absolutely dependent on angiogenesis with vascular endothelial growth factor (VEGF) being the most important cytokine involved in the process. Endoglin, a membrane co-receptor for TGF-beta, has recently emerged as a sensitive index of cancer stage. There is now sufficient evidence indicating that microvessel density assessed by endoglin-immunostaining correlates with stage of colorectal cancer and patient survival. An association of a soluble form of endoglin with lymph node and distant metastases has recently been reported in two studies. Both of them used local elaborated immunoassays for endoglin assessment. The aim of our study was to determine the efficacy of plasma endoglin, assessed using a commercial kit, as a marker of tumor spread and distant metastases in colorectal cancer patients. We studied 48 colorectal cancer patients, compared with 22 healthy subjects, using ELISA. We observed that colorectal cancer patients had increased plasma VEGF-A, but not endoglin levels. However, we found an association of plasma endoglin with the stage of malignancy. Endoglin levels were increased in metastasis-positive patients when compared to both metastasis-negative patients and healthy volunteers. Plasma endoglin correlated with VEGF-A, CEA and CA19.9. Endoglin assessment in plasma does not seem useful as a maker of colorectal cancer. Our observations indicate however that it might be helpful in selecting patients with metastatic disease.